Analisis Penggunaan Media Sosial TikTok dalam Pembelajaran Pendidikan Agama Islam Kelas XI di SMA Negeri 1 Patamuan - Efendi, Yoserizal (TSAQOFAH, 2025)
This study is motivated by technological developments that have driven increased use of social media among students, including TikTok, which was initially used for entertainment but is now utilized in education, particularly in Islamic Religious Education (Pendidikan Agama Islam, PAI) learning. The research aims to examine the use of TikTok as a PAI learning medium among Grade XI students at SMA Negeri 1 Patamuan. A qualitative descriptive method was employed, with data collected through in-depth interviews with teachers and students, observation of learning activities, and documentation of class activities. The analysis focused on identifying the role of TikTok in the planning, implementation, and evaluation stages of learning. The results show that in the planning stage, teachers design PAI material concepts aligned with the curriculum, package them into short educational videos, select relevant themes, and choose media that attract learning interest. In the implementation stage, students are directed to access and study TikTok content with religious themes such as dakwah, Qur’anic verse quotations, Islamic advice, and worship practices. The evaluation stage involves assessing students’ video works or analyses based on content, creativity, and understanding, as well as class discussions and reflections. The study concludes that using TikTok as a PAI learning medium can increase student engagement, enrich learning resources, and provide a more interactive learning experience.